Chula Formula is recommended in Estimating the Length of Tracheal Tube Insertion in Patients Receiving Mechanical Ventilation in Intensive Care Units in the Absence of Chest X-Ray - Laksono, Buyung Hartiyo; Hartono, Ruddi; Tamam, Abdul Rasyid; Jaya, Wiwi (Faculty of Medicine, Brawijaya University, 2023)
Background: Chest X-Ray (CXR) is one of the most effective ways of confirming the length of the tracheal tube (TT) insertion. However, some intensive care unit in developing countries has no sufficient facilities. This study aims to evaluate the accuracy of TT length insertion using the Chula formula and Colombian formula in patients receiving mechanical ventilation in intensive care units.Methods: This study is a comparative observational study of 50 adults in the Intensive care unit, divided into two groups. Group A used the Chula formula for TT length insertion (n= 25) and Group B used the Colombian formula (n= 25). The TT length insertion accuracy was evaluated using radiological parameters. Statistical analysis used: Data were analyzed statistically using the T-test and Chi-square test.Result: The Chula formula is significantly more precise than the Colombian formula in estimating the length of TT insertion based on the radiographic parameters of the TT length insertion right midway between the medial tip of the clavicle and TT located in the T3 or T4 vertebrae (p <0.05), but not significantly different in the two other parameters.Conclusion: Both the Chula formula and the Colombian formula can estimate the length of TT insertion in adult patients. However, the Chula formula is more recommended in the length of TT insertion and benefit in the ICU with insufficient CXR.